Acute and Chronic Effects of Endurance Running on Inflammatory Markers: A Systematic Review - Barros, Edilberto S.; Nascimento, Dahan C.; Prestes, Jonato; Nóbrega, Otávio T.; Córdova, Claúdio; Sousa, Fernando; Boullosa, Daniel A. (Frontiers in Physiology, 2017)
In order to understand the effect of endurance running on inflammation, it is necessary to quantify the extent to which acute and chronic running affects inflammatory mediators. The aim of this study was to summarise the literature on the effects of endurance running on inflammation mediators. Electronic searches were conducted on PubMED and Science Direct with no limits of date and language of publication. Randomized controlled trials (RCTs) and non-randomized controlled trials (NRCTs) investigating the acute and chronic effects of running on inflammation markers in runners were reviewed by two researchers for eligibility. The modified Downs and Black checklist for the assesssments of the methodological quality of studies was subsequently used. Fifty-one studies were finally included. There were no studies with elite athletes. Only two studies were chronic interventions. Results revealed that acute and chronic endurance running may affect anti- and pro-inflammatory markers but methodological differences between studies do not allow comparisons or generalization of the results. The information provided in this systematic review would help practitioners for better designing further studies while providing reference values for a better understanding of inflammatory responses after different running events. Further longitudinal studies are needed to identify the influence of training load parameters on inflammatory markers in runners of different levels and training background.